Diet of Iheringichthys labrosus (Pimelodidae, Siluriformes) in the Itaipu Reservoir, Paraná River, Brazil-Paraguay - Abes,Sara da Silva (2001)
Iheringichthys labrosus is a secondary commercial fish species in the Itaipu Reservoir, but it is important in other reservoirs of the basin. However, little information exists about this species in the literature. The purpose of this study was to describe the diet of this species in the Itaipu Reservoir. Stomachs of 306 fishes were analyzed, collected from October 1994 to September 1996 in the differents zones of the reservoir (according to a longitudinal gradient). The reservoir was separated into riverine (upper reach), transitional (middle reach), and lacustrine (next to the dam) zones. Main items in the diet of I. labrosus were aquatic insects (mainly Chironomidae) and mollusks (mainly Bivalvia). Their presence in the diet did not vary according to zones. Also, there was little seasonal variation in the diet. This indicated a conservative diet that could be a result of the high abundance of the items in the reservoir, or restrictions imposed by its buccal and digestive apparatus.